Effect Of Employee's Motivation And Performance With Job Satisfaction As A Mediation Variable On Cooperative Units Village, Kampung Rakyat District - Shella Agustin; Pitriyani, Pitriyani; Prayoga, Yudi (Publisher Cv. Inara, 2022)
This study aims to answer the influence of employee motivation and performance with job satisfaction as a mediating variable in the village unit cooperative, Kampung Rakyat sub-district. Data collection was carried out by distributing questionnaires to 35 members of the Kampung Rakyat cooperative. This study uses quantitative methods and performs data processing with the tools of IBM SPSS Statistic 22. This analysis includes reliability tests, validity tests, classical assumption tests, statistical tests, multiple linear regression tests and moderation tests using Moderated Regression Analysis (MRA). The results of the tests conducted in this study indicate that job satisfaction (M) can moderate the effect of motivation (X1) on employee performance (Y). These results are shown through the regression equation with the interaction test or often referred to as Moderated Regression Analysis (MRA) which shows the results that job satisfaction (M) influences or moderates the effect of motivational variables (X1) on employee performance (Y). The results of the t test show that the motivation variable (X1) provides a parameter coefficient value (?) of 0.012 with a significant level of 0.027 (significant), the job satisfaction variable (M) provides a parameter coefficient value (?) of 0.023 and a significant value of 0.000 (significant). ). Or in other words job satisfaction strengthens the influence of motivation on employee performance. Thus, the results of this study can prove hypothesis 2 that job satisfaction moderates the effect of motivation on employee performance.